Effects of galvanic vestibular stimulation on bodily ownership and postural control: An experimental examination with counterbalanced randomization of stimulus conditions - Kerem Ersin; Berna Özge Mutlu (PLoS ONE, 2026)
Vestibular stimulation influences both bodily ownership and postural control. Although previous studies in the literature have examined the effects of galvanic vestibular stimulation (GVS) on body ownership and balance separately, their combined and time-dependent effects remain insufficiently explored. This study investigated how GVS modulates multisensory integration over time by assessing bodily ownership and postural control within the same participants. A within-participant design was used with four conditions: Baseline (pre-GVS), Sham (60-min post-GVS placebo), 30-min post-GVS, and 60-min post-GVS. Forty-eight healthy adults completed all conditions. Balance performance was assessed via the Single-Leg Stance (SLS) and Fukuda Stepping Test (FST), while bodily ownership was measured using the Rubber Hand Illusion (RHI) questionnaire. Balance performance on the SLS showed a significant reduction at 30 minutes post-GVS, with values returning toward baseline by 60 minutes. In contrast, angular deviation on the FST decreased significantly at both 30 and 60 minutes post-GVS. RHI ownership scores increased at both post-stimulation time points, with the most pronounced increase observed at 60 minutes. The sham condition also elicited increases in RHI scores, indicating possible expectancy-related effects. Overall, these findings indicate time-dependent and task-specific effects of GVS on bodily ownership and postural control. The results are consistent with adaptive sensory reweighting processes that differentially affect static and dynamic balance measures. Further research in clinical populations and using longer stimulation protocols is required to determine the extent to which these short-term effects translate into sustained functional benefits.